JANE AUSTEN'S NOVELS AND TELUGU CINEMA: A COMPARATIVE STUDY OF SOCIAL CLASS AND ROMANTIC COMPATIBILITY - Alapati, Hemalatha; Sarkhel, Ranjana Das (ShodhKosh: Journal of Visual and Performing Arts, 2024)
With an eye towards the convergences and divergences between these two narrative traditions, this article seeks to examine and compare the representation of social class and romantic compatibility in Austen's literary works with their Telugu film counterparts. This paper looks at how Telugu movies and Jane Austen's writings portray social class and romantic compatibility. Both Telugu cinema and Austen's literary works often run across issues with social stratification and the framework of romantic relationships, although in quite different historical and cultural contexts. Early in the 19th century, Jane Austen's works offer a critical study of social class and love compatibility inside England under Regency. Reflecting the social and cultural dynamics of South India, The Telugu films also grapple with these topics, usually by merging traditional and modern narrative elements. By contrasting Austen's subdued treatment of these issues with their portrayal in Telugu movies, this study reveals how society conventions and storytelling traditions affect the management of class and romance in both mediums. The relationship between social class and love compatibility in the works of Jane Austen's books and Telugu film is investigated by means of a comparative analysis.